Annexin A1: A Central Player in the Anti-Inflammatory and Neuroprotective Role of Microglia - McArthur, Simon (2010)
The brain microenvironment is continuously monitored by microglia with the detection of apoptotic cells or pathogens being rapidly followed by their phagocytosis to prevent inflammatory responses. The protein annexin A1 (ANXA1) is key to the phagocytosis of apoptotic leukocytes during peripheral inflammatory resolution, but the pathophysiological significance of its expression in the CNS that is restricted almost exclusively to microglia is unclear. In this study, we test the hypothesis that ANXA1 is important in the microglial clearance of apoptotic neurons in both noninflammatory and inflammatory conditions. We have identified ANXA1 to be sparingly expressed in microglia of normally aged human brains and to be more strongly expressed in Alzheimer's disease. Using an in vitro model comprising microglial and neuronal cell lines, as well as primary microglia from wild-type and ANXA1 null mice, we have identified two distinct roles for microglial ANXA1: 1) controlling the noninflammatory phagocytosis of apoptotic neurons and 2) promoting resolution of inflammatory microglial activation. In particular, we showed that microglial-derived ANXA1 targets apoptotic neurons, serving as both an “eat me” signal and a bridge between phosphatidylserine on the dying cell and formyl peptide receptor 2 on the phagocytosing microglia. Moreover, inflammatory activation of microglia impairs their ability to discriminate between apoptotic and nonapoptotic cells, an ability restored by exogenous ANXA1. We thus show that ANXA1 is fundamental for brain homeostasis, and we suggest that ANXA1 and its peptidomimetics can be novel therapeutic targets in neuroinflammation.